Pre-service Military-related and Mental Disorder Factors Associated with Leaving the UK Armed Forces. Issue 3 (2nd July 2020) - Burdett, Howard; Stevelink, Sharon A. M.; Jones, Norman; Hull, L.; Wessely, Simon; Rona, Roberto
Abstract : Background : The UK Armed Forces (UKAF) have a substantial manning deficit as more personnel leave than join. This article identified pre-service, military, and mental health factors giving rise to leaving the UKAF and estimated the contributions to leaving of those factors which are potentially amenable to modification. Methods : This study utilized data from a three-phase cohort study (2004–2006, 2007–2009 and 2014–2016), commencing while respondents were serving in the UKAF (n = 10, 836; 6, 046 (55.8%) had left service). Associations between leaving the services and socio-demographics, military career and experiences, and mental health were determined using Cox regression. Contribution to leaving was based on population attributable fractions (PAF) from Cox regression. Analyses were stratified by rank due to the different career structures of Commissioned Officers and enlisted personnel. Results : Leaving the UKAF was associated with joining when older, being a woman with a child/children, Army service, combat role, lower education level, and poor mental health. Factors contributing a significant proportion of leaving among enlisted personnel were joining over the age of 17, history of externalizing behavior, being female, common mental disorders, and alcohol misuse. Among Commissioned Officers only age at joining and sex contributed significant proportions to leaving. Conclusions : The key factors for leaving are education and higher age at recruitment. These are not amenable to intervention, for policy, equity, and legal reasons. Heavy drinking and common mental disorder symptoms may be more amenable to modification and hence reduce rates of leaving the UKAF. Women are more likely to leave due to childbearing.